O INSTITUTO-GARANTIA DA CAUÇÃO AMBIENTAL E A COMPETÊNCIA LEGISLATIVA CONCORRENTE NA RELAÇÃO FEDERATIVO-CONSTITUCIONAL ENTRE O ESTADO DE MINAS GERAIS E A UNIÃO - Oliveira, Márcio Luís de; Costa, Beatriz Souza (Veredas do Direito, 2021)
The objective of the essay was to analyze the environmental bond required in the licensing processes for economic mining activities and the use of dams. The study legally classified the environmental bond as a guarantee for diffuse rights. Such guarantee applies to the duty of assistance and repair for possible environmental disasters and their respective humanitarian and cultural consequences. The work concluded that, within the scope of the Brazilian federation, the specific state law or the federal framework law that best meets the constitutional principles of the most effective protection and federal subsidiarity must prevail. The methodology used in the research was deductive, analytical, dogmatic and comparative; and national, state and foreign legislation and specific bibliographic texts were consulted.